Doctor, teacher, terrorist: the life and legacy of Al-Qaeda leader Ayman al-Zawahiri - Gohel, Sajjan M. (Oxford University Press, 2024)
For over half a century, al-Qaeda leader Ayman al-Zawahiri repeatedly emerged from the shadows as a vengeful ideologue hell-bent on changing history. Dr. Sajjan M. Gohel provides the first definitive account of one of the world's most wanted terrorists. Having grown up in an illustrious Egyptian family of physicians, lawyers, clergy, and politicians, al-Zawahiri was originally destined to become a successful doctor. However, he chose to rebel against his own society which he deemed to have deviated from its religious identity. By forming his own terrorist group, al-Zawahiri dedicated his life to sedition and violent rebellion against the international order. Ayman al-Zawahiri led a life incomparable to anyone else. The Egyptian found himself in many of the places where history was being determined. His journey takes us across Egypt, Sudan, Afghanistan and Pakistan, as well as the United States and Russia. Through his close bond with Osama bin Laden, al-Zawahiri played a critical role in the evolution of al-Qaeda's ideology, recruitment, tactics, and strategy. With the deft touch of a teacher, al-Zawahiri delegated numerous murderous assignments globally. He engaged in the assassination of political leaders, sought to develop chemical and biological weapons, recruited double and triple agents, turned the tables on his enemies, and pioneered the use of new media technology to convey al-Qaeda's zealotry. In 2011, al-Zawahiri succeeded bin Laden, to become the head of al-Qaeda and sought to rebuild and reform his organisation whilst being aided by murky ties in Pakistan and Iran and his Taliban allies. Against the background of the Arab Spring and the West's departure from Afghanistan, al-Zawahiri left a deadly legacy for al-Qaeda's future for years to come.